Bladder Mucosal Cystitis Cystica Lesions Are Tertiary Lymphoid Tissues That Correlate With Recurrent Urinary Tract Infection Frequency in Postmenopausal Women. Issue 5 (30th May 2023) - Ligon, Marianne M.; Liang, Brooke; Lenger, Stacy M.; Parameswaran, Priyanka; Sutcliffe, Siobhan; Lowder, Jerry L.; Mysorekar, Indira U.
Abstract : Purpose: We identify correlates and clinical outcomes of cystitis cystica, a poorly understood chronic inflammatory bladder change, in women with recurrent urinary tract infections. Materials and Methods: A retrospective, observational cohort of women with recurrent urinary tract infections who underwent cystoscopy (n=138) from 2015 to 2018 were identified using electronic medical records. Cystitis cystica status was abstracted from cystoscopy reports and correlations were identified by logistic regression. Urinary tract infection–free survival time associated with cystitis cystica was evaluated by Cox proportional hazards regression. Exact logistic regression was used to identify factors associated with changes to cystitis cystica lesions on repeat cystoscopy. Biopsies of cystitis cystica lesions were examined by routine histology and immunofluorescence. Results: Fifty-three patients (38%) had cystitis cystica on cystoscopy. Cystitis cystica was associated with postmenopausal status (OR: 5.53, 95% CI: 1.39-37.21), pelvic floor myofascial pain (6.82, 1.78-45.04), having ≥4 urinary tract infections in the past year (2.28, 1.04-5.09), and a shorter time to next urinary tract infection (HR: 1.54, 95% CI: 1.01-2.35). Forty-two patients (82%) demonstrated improvement or resolution of lesions. Ten/11 (91%) biopsied cystitis cystica lesions were tertiary lymphoid tissue with germinal centers and resembled follicular cystitis. Conclusions: Cystitis cystica lesions were associated with postmenopausal status, pelvic floor myofascial pain, and number of urinary tract infections in the prior year and predicted worse recurrent urinary tract infection outcomes. Cystitis cystica lesions are tertiary lymphoid tissue/follicular cystitis that may improve or resolve over time with treatment. Identifying cystitis cystica in recurrent urinary tract infection patients may be useful in informing future urinary tract infection risk and tailoring appropriate treatment strategies.